The linguistic study of works of Janka Kupala and Jakub Kolas in 1920 –50s - Zaprudski, Siarhiej M. (Journal of the Belarusian State University. Philology, 2019)
The article deals with the origin of linguistic study of Kupala and Kolas’ works as an independent research field. The first attempts to study the language of the classics evaluated their language as an important component of the national language as a whole; they also illustrated the history of the Belarusian language in its written form. It was very difficult to achieve continuity between studies of different times during the analysed period. In the post-war years the dominant subjects of literary scholars’ studies were «Kupala and Kolas as the creators of the Belarusian literary language» and «The connection of the language in works of Kupala and Kolas with the vernacular language». Over time, the linguists began to define the language of the writers as a classic one, which was important both for the history of the Belarusian language and for the present time. The approach to study the classics’ language as a modern one was a priority because the formation of Kupala and Kolas linguistic study was happening mostly during the development of the standard Belarusian language study that was modern language focused. The categories and approaches formulated by the Belarusian synchronic linguistics – for example defining certain words as dialectisms, Russicisms, Polonisms, etc. – were adopted in the studies about the language of Kupala and Kolas over time. It was an essential aspect of Kupala and Kolas study evolution in the post-war period to implicitly distinguish two periods in their creative work, a beginning period and main period; the classics were mastering their skill during the first one and were forging major features of their language during the second one.